Chirality in the Absence of Rigid Stereogenic Elements: Steric and Electronic Effects on the Configurational Stability of C3 Symmetric Residual Tris‐Aryl Phosphanes. Issue 10 (7th March 2014) - Rizzo, Simona; Cirilli, Roberto; Pierini, Marco
ABSTRACT Residual stereoisomers result whenever closed subsets of appropriately substituted interconverting isomers (the residual stereoisomers) are generated from a full set of stereoisomers under the operation of a favored stereomerization mechanism. In the case of the three‐bladed propellers, differentiation of the edges of the blades and strict correlation in the motion of the rings are the prerequisites for the existence of residual stereoisomers. In these systems, the two‐ring flip mechanism is the lowest energy process. It does not interconvert all possible conformational stereoisomers generated by helicity and the three‐blade‐hub rotors. In the case of C3 symmetric systems, two noninterconverting subgroups (the residual stereoisomers) are generated, each one constituted of quickly interconverting diastereoisomers. A series of tris‐aryl phosphanes, structurally designed for existing as residual enantiomers or diastereoisomers, bearing substituents differing in size and electronic properties on the aryl rings, were synthesized and characterized. The configurational stability of residual phosphanes, evaluated by dynamic 1H‐ and 31P‐NMR analysis and by dynamic enantioselective high‐performance liquid chromatography (HPLC), was found 10 kcal mol‐1 lower than that shown by the corresponding phosphane‐oxides. In accordance with the calculations, an unexpectedly low barrier for phosphorus pyramidal inversion was invoked as responsible for the scarce configurational stability of the residual tris‐arylphosphanes. Chirality 26:601–606, 2014. © 2014 Wiley Periodicals, Inc.